Award for Best Oral Presentation by a First Timer - Hunting zebra: retrieving rare disease guidelines (Journal of EAHIL, 2017)
The EAHIL 2014 conference provided the opportunity to present a piece of work carried out by a team of informationprofessionals for RARE-Bestpractices (RBP), an international project to promote exchange of information andknowledge in rare disease. The authors work for Healthcare Improvement Scotland (HIS), a publicly fundedorganisation which uses evidence, scrutiny and improvement science to facilitate the delivery of safe, effective andpatient-centred healthcare. HIS is one of fifteen European partners contributing to RBP with our team providing thecore information professional support for the project. Work to develop a rare disease guideline search protocol waspresented in order to raise awareness of RARE-Bestpractices, and to demonstrate the engagement of informationprofessionals in multidisciplinary research projects.